Peran Rumah Literasi Pinggir Sawah di Daerah Sempu Banyuwangi Dalam Pembentukan Kesadaran Lingkungan - Wardani, Rizki Putri; Fitriyah, Chumi Zahroul; Rofiq, Annur (Learning Community : Jurnal Pendidikan Luar Sekolah, 2023)
The aim of this research is to determine the role of the Pinggir Sawah Literacy House in the Sempu Banyuwangi area in terms of forming environmental awareness. The research method used is descriptive with a qualitative approach. The technique used was in-depth interviews by digging up information from data sources from the Pinggir Sawah administrators and the community who came to the place. The research results illustrate that the role of the Pinggir Sawah literacy house is able to raise awareness of love for the environment. Some activities include utilizing waste, planting plants using organic media. The role of the Pinggir Sawah literacy house is to try to create environmental awareness by reducing waste and utilizing it to create a clean and healthy environment. Activities carried out include outreach and training in waste utilization skills